Users’ Attitudes towards Institutional Repository in Jadavpur University: A Critical Study - Halder, Sambhu Nath; Chandra, Suvra (International Journal of Management and Sustainability, 2012)
This paper examines the user-aware of institutional repositories in Jadavpur University. The main objective of this study is to investigate the awareness of Institutional Repository (IR) in an academic institution and different aspects associated with it, such as, software, sources for user’s awareness, motivators for developing a repository, demand of the users in changing paradigms from traditional to digital environment, etc. In the present days, libraries are also adopting the latest technologies to provide best possible services in user friendly form. This paper also describes the potential role of institutional repositories and its easiness and simplicity of use are attracting more patrons in the use of institutional repositories. Only a wide range of user awareness is needed for proper usage of its beauty. Entirely this paper is based on a critical study, which measures the utility of institutional repositories in users’ point of view.